Drug utilisation pattern of antihistamines in upper respiratory tract infections in paediatric patients - Bharati, Jyoti Prabha; Ulak, Sanjay; Keshari, Aniket; Acharya, Anna (Journal of Kathmandu Medical College, 2021)
Background: Upper respiratory tract infections (URTIs) are the most common infections in the paediatric population leading to health care consultations. Antihistamines are commonly prescribed medicines in children. Objectives: This study attempted to assess the current prescription patterns of antihistamines used in the treatment of URTIs. Methods: A descriptive cross-sectional study was conducted in the outpatient paediatric department of Kathmandu Medical College from January 2020 to April 2021. Ethical approval was taken from Institutional Review Committee of Kathmandu Medical College. A convenient sampling technique was used. The data were collected from the outpatient department prescription card into a suitably designed proforma. Drug use indicator developed by the World Health Organisation for Rational Use of Drugs was utilised. Data were analysed using SPSS v.20. Results: Data from prescriptions of 345 patients aged less than 14 years were collected from the paediatric outpatient department of KMCTH. The most common condition was common cold (132, 38.26%). Most commonly prescribed antihistamines were Fexofenadine (156, 45.21%). Average number of drugs per prescription was 2.31. The total number of drugs prescribed by generic name was 128 (16%). Antibiotics made its place in prescriptions 279 (34.96%) times. No parenteral medication was used and 140 (17.5 %) of all drugs prescribed were from the National List of Essential Medicines. Conclusion: Antihistamines, mostly second generation, were commonly prescribed in URTIs in paediatric patients. Majority of WHO indicators were within normal limits while some needed marked improvement. Different programmes can be implemented for improvement in prescribing patterns and promotion of rational drug use.